Порівняльне дослідження ризогенезу живців малопоширених видів та культиварів деревних рослин у Донбасі - Довбиш, Н.Ф.; Хархота, Л.В. (Промышленная ботаника, 2006)
Comparative researches data of some species and cultivars of ornamental arboreal decidous plants cutting rhizogeny are given with the aim of success forecasting of their artifical reproduction in Donbass amenity planting. It is fixed, that species regeneration ability and its cultivars regeneration ability are similar.